Atonement and the Logic of Resurrection in the Epistle to the Hebrew s - Moffitt, D. M. (Novum Testamentum, Supplements, 2011)
Scholars often explain Hebrews' relative silence regarding Jesus' resurrection by emphasizing the author's appeal to Yom Kippur's two key moments-the sacrificial slaughter and the high priest's presentation of blood in the holy of holies-in his distinctive portrayal of Jesus' death and heavenly exaltation. The writer's depiction of Jesus as the high priest whose blood effected ultimate atonement appears to be modeled upon these two moments. Such a typology discourages discrete reflection on Jesus' resurrection. Drawing on contemporary studies of Jewish sacrifice (which note that blood represents life, not death), parallels in Jewish apocalyptic literature, and fresh exegetical insights, this volume demonstrates that Jesus' embodied, resurrected life is crucial for the high-priestly Christology and sacrificial soteriology developed in Hebrews.